2018
DOI: 10.1021/acs.est.8b01876
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical Controls on Strontium Fate at the Sediment–Water Interface of Two Groundwater-Fed Wetlands with Contrasting Hydrologic Regimes

Abstract: Radioactive strontium (Sr) is a common groundwater contaminant at many nuclear sites. Its natural retention in groundwater-fed wetlands is an attractive remediation strategy. However, at present, the biogeochemical mechanisms controlling Sr transport at the sediment-water interface are poorly understood. In this field study, Sr fate was investigated in two wetlands with contrasting vegetation and hydrologic regimes. The marsh was an open-water wetland with constant water table and no emergent vegetation. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…In this study, we demonstrated that fresh SGD is an important but overlooked source of 90 Sr in the coastal ocean, which may partly address the issue that has remained unanswered in previous studies, namely, surplus 90 Sr has consistently been found in coastal oceans, but no clear evidence of an additional 90 Sr source has been determined. , Notably, the 90 Sr level in fresh groundwater measured in this study is much lower than the drinking water limit of the World Health Organization (WHO) (10 4 Bq m –3 ), and thus, its effect on public health is not of primary concern here. However, due to its high mobility, 90 Sr is a ubiquitous and troublesome anthropogenic radionuclide in groundwater around nuclear facilities. , Extremely high 90 Sr levels have been found in groundwater near nuclear facilities and nuclear test sites worldwide (Table ). For example, the 90 Sr activity in groundwater near the FDNPP reached as high as 5 × 10 9 Bq m –3 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, we demonstrated that fresh SGD is an important but overlooked source of 90 Sr in the coastal ocean, which may partly address the issue that has remained unanswered in previous studies, namely, surplus 90 Sr has consistently been found in coastal oceans, but no clear evidence of an additional 90 Sr source has been determined. , Notably, the 90 Sr level in fresh groundwater measured in this study is much lower than the drinking water limit of the World Health Organization (WHO) (10 4 Bq m –3 ), and thus, its effect on public health is not of primary concern here. However, due to its high mobility, 90 Sr is a ubiquitous and troublesome anthropogenic radionuclide in groundwater around nuclear facilities. , Extremely high 90 Sr levels have been found in groundwater near nuclear facilities and nuclear test sites worldwide (Table ). For example, the 90 Sr activity in groundwater near the FDNPP reached as high as 5 × 10 9 Bq m –3 .…”
Section: Resultsmentioning
confidence: 99%
“…There are currently more than 200 nuclear power plants situated along coastlines worldwide . Despite stricter environmental and safety regulations, the expected increase in global nuclear electricity production by 2050 may lead to 90 Sr contamination at more sites. , Thus, we suggest that the subterranean pathway for the release of 90 Sr into the coastal ocean should be considered in the management and risk assessment of coastal areas near nuclear power plants. Furthermore, the implications of our findings could extend beyond 90 Sr to other highly mobile radionuclides (such as 3 H and 129 I).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations